Cellular anatomy of the mouse primary motor cortex - Muñoz-Castañeda, Rodrigo; Zingg, Brian; Matho, Katherine S.; Chen, Xiaoyin; Wang, Quanxin; Foster, Nicholas N.; Li, Anan; Narasimhan, Arun; Hirokawa, Karla E.; Huo, Bingxing; Bannerjee, Samik; Korobkova, Laura; et al. (Nature (London), 2021)
An essential step toward understanding brain function is to establish a structural framework with cellular resolution on which multi-scale datasets spanning molecules, cells, circuits and systems can be integrated and interpreted 1 . Here, as part of the collaborative Brain Initiative Cell Census Network (BICCN), we derive a comprehensive cell type-based anatomical description of one exemplar brain structure, the mouse primary motor cortex, upper limb area (MOp-ul). Using genetic and viral labelling, barcoded anatomy resolved by sequencing, single-neuron reconstruction, whole-brain imaging and cloud-based neuroinformatics tools, we delineated the MOp-ul in 3D and refined its sublaminar organization. We defined around two dozen projection neuron types in the MOp-ul and derived an input–output wiring diagram, which will facilitate future analyses of motor control circuitry across molecular, cellular and system levels. This work provides a roadmap towards a comprehensive cellular-resolution description of mammalian brain architecture. Multi-modal analysis is used to generate a 3D atlas of the upper limb area of the mouse primary motor cortex, providing a framework for future studies of motor control circuitry.